Measuring quality and patient satisfaction in healthcare communication with foreign-language speakers - Bischoff, Alexander (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Healthcare services face increasing challenges to provide accessible care to an equally increasing diversity ofpatient populations. This is clearly reflected in the linguistic diversity ofpeople living in Switzerland and can be seen mostplainly in the country ’s public hospitals. After a literature review on language barriers in clinical services and the potential impact that interpreters can have in clinical outcomes, we describe how interpreters can be introduced in a primary care setting and how the quality of communication with foreign-language-speaking patients as well as their satisfaction with communication can be improved. Changes in the quality of inter - preter-mediated communication, as rated by the patients themselves, can be monitored and have a beneficial impact on the quality of care. This is important at a time of growing cultural and linguistic diversity in Switzerland and other countries, which requires healthcare systems to implement highquality professional interpreter services that ensure effective communication withforeign-language-speakingpatients.